Alloys-by-design: applications to polycrystalline nickel superalloys for turbine disc applications - Crudden, DJ (2014)
The nickel-based superalloys have been a key enabler to the development of modern gas turbine engines. Since their introduction the chemical complexity of these alloys has increased significantly, with current generation nickel-based superalloys usually containing over 10 different elements. It is this combination of alloying additions that is responsible for the superior high temperature properties these alloys exhibit. Traditionally, alloy design has invoked considerable use of trial-and-error based approaches involving costly and exhaustive processing backed up by empirical property testing. In this work a computational materials design approach is developed. This method links physically-faithful composition-dependent models with thermodynamic calculations to understand material behaviour. By doing this it is possible to consider large compositional design spaces and isolate alloys expected to have optimal performance for specific applications. The scope of this research has been to apply the computational model to the design of a polycrystalline nickel-based superalloy for turbine disc applications in next generation jet engines. The design trade-offs encountered when developing the new alloy are highlighted. Alloy compositions which are predicted to be optimal for turbine disc applications are isolated. These alloys have been manufactured using a scaled down version of the commercial production method. The newly manufactured alloys have been characterised using microstructural evaluation, mechanical testing and corrosion testing. The experimental results have been compared with modelling predictions in order to determine the capability of the computational approach.